Toxicity and Biodegradation in Sandy Soil Contaminated by Lubricant Oils - Lopes, Paulo Renato Matos; Montagnolli, Renato Nallin; de Fátima Domingues, Renata; Bidoia, Ederio Dino (Bulletin of environmental contamination and toxicology, 2010)
The objective of this study was to evaluate the environmental behavior of different types of automotive lubricant oils. Based on respirometry assays the biodegradability was monitored, and toxicological tests were executed to assess the lubricants toxicity before and after microbial activity. Used oil was the most biodegradable, however, it was the most toxic. Also, all lubricants presented toxicity even after biodegradation due to 40% Eruca sativa germination inhibition and a low LC50 to Eisenia foetida (0.50-0.25 mL). Moreover, used automotive lubricants have a high toxicity because of polycyclic aromatic hydrocarbons concentration that establishes them as a potential carcinogen.